THE EFFECT OF PICTURE SERIES TOWARD STUDENTS’ DESCRIPTIVE WRITING SKILL - Nina Puspitaloka (JUDIKA (JURNAL PENDIDIKAN UNSIKA), 2016)
The objective of this study are to find out the significant effect of the use Picture Series students’ descriptive writing skill and the students’ responses toward using Picture Series in writing descriptive text. This research used quantitative method with quasi experimental design. The target population and sample of this study was the tenth grade of students at Private Senior High School in Karawang that consist of 60 students. In this research, written test was administered as an instrument for both experimental and control groups and the administrating of questionnaires given to an experimental group. To answer the first research problem, the data from written test were analyzed using independent t-test. The result of data was of tobserved = 2.037 and ttable = 2.00 with the standard of significance 0.05. It means that tobserved was higher than the ttable (2.037 > 2.00). Moreover, the result indicated that Picture Series media significantly was effective toward students’ descriptive writing skill. Based on the result of questionnaire, it can be explained that most of the students had positive responses in learning writing of descriptive text by using Picture Series media and they were felt enjoyable and interested series to use pictures  in learning writing descriptive text.Keywords: Descriptive Writing Skill, Picture Series.